2015
DOI: 10.1371/journal.pone.0121875
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative Hyphal Fusion and Subsequent Nuclear Behavior in Epichloë Grass Endophytes

Abstract: Epichloë species (including the former genus Neotyphodium) are fungal symbionts of many agronomically important forage grasses, and provide their grass hosts with protection from a wide range of biotic and abiotic stresses. Epichloë species include many interspecific hybrids with allodiploid-like genomes, which may provide the potential for combined traits or recombination to generate new traits. Though circumstantial evidence suggests that such interspecific hybrids might have arisen from nuclear fusion event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 95 publications
(135 reference statements)
0
13
0
Order By: Relevance
“…Instead of undergoing meiosis, the vegetative cells continue dividing mitotically, and haploidy is restored by random chromosome loss resulting in cells with unique combinations of chromosomes from either parent nucleus. Many fungi that have never been observed to mate in their natural environment are still capable of parasexuality [ 215 , 216 ]. Furthermore, it has been shown that the thin-walled blastospores Metarhizium produces in insect haemolymph may facilitate genetic exchange between isolates co-infecting an insect [ 217 ].…”
Section: Sexuality and Host Rangementioning
confidence: 99%
“…Instead of undergoing meiosis, the vegetative cells continue dividing mitotically, and haploidy is restored by random chromosome loss resulting in cells with unique combinations of chromosomes from either parent nucleus. Many fungi that have never been observed to mate in their natural environment are still capable of parasexuality [ 215 , 216 ]. Furthermore, it has been shown that the thin-walled blastospores Metarhizium produces in insect haemolymph may facilitate genetic exchange between isolates co-infecting an insect [ 217 ].…”
Section: Sexuality and Host Rangementioning
confidence: 99%
“…Whether these shifts resulted from selection acting on nuclei [ 14 ] or from more random processes of gain or loss in particular mycelial fractions requires further investigation. Recently, it has been shown that heterokaryons and subsequent hybrids can form between different strains of the grass endophyte, Epichloë , through vegetative hyphal fusion [ 15 ]. In fact, the existence of multiple genotypically distinct nuclei within the same mycelium may be more common than is recognized, particularly among filamentous ascomycetes [ 16 ].…”
Section: Heterokaryons and Adaptationmentioning
confidence: 99%
“…lolii ) or from interspecific hybridizations between sexual and/or asexual Epichloë species (Craven, 2003). Hybridizations may occur within host plants that are co-infected by different strains through a process known as vegetative hyphal fusion (VHF) or anastomosis followed by nuclear fusion (Shoji et al, 2015). Interspecific hybrids have an allopolyploid-like genome which is the result of the combination of two or more parental chromosome sets.…”
Section: Introductionmentioning
confidence: 99%